International Cooperative Test on Texture of Cooked Rice - Juliano, Bienvenido O.; Perez, Consuelo M.; Alyo-Shin, E.P.; Romanov, V.B.; Blakeney, Anthony B.; Welsh, Lynsey A.; Choudhury, Nurul H.; Lilia Delgado, L.; Iwasaki, Tetsuya; Shibuya, Naoto; Mossman, Albert P.; Siwi, Bernard; et al. (Wiley, 1984)
i